Search for CP violation in Λb0→pK− and Λb0→pπ− decays; Physics Letters B; Vol. 787 - Aaij R. Roel; Adeva B. Bernardo; Adinolfi M. Marco; Aidala C. Christine; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich; Vagner A. R. Aleksandr Rudolfovich (2018, 2018)
Title screen